1919 Mass. Acts 139 - (:unkn) unknown (My University, 1919)
An Act Relative to the Issuance of Search Warrants for the Seizure of Firearms, Weapons and Ammunition Kept for Unlawful Purposes, ch. 179, §§ 1-2: A court or justice authorized to issue warrants in criminal cases may, upon complaint under oath that the complainant believes that an unreasonable number of rifles, shot guns, pistols, revolvers or other dangerous weapons, or that an unnecessary quantity of ammunition, is kept or concealed for any unlawful purpose in a particular house or place, if satisfied that there is a reasonable cause for such belief, issue a warrant to search such property. § 2. If the court or justice finds that such property is kept for an unlawful purpose, it shall be forfeited and disposed of as the court or justice may by order direct.
Keywords: POSSESSION